Access To Capital For Micro, Small, and Medium Enterprises (MSMES/UMKM) Through Formal and Informal Financial Institutions - Adhis Darussalam Pamungkas; Rudi Bratamanggala (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines Micro, Small, and Medium Enterprises (MSMEs) access to capital from formal and non-formal financial institutions in Indonesia. Using a qualitative approach through in-depth interviews with 30 MSME actors in three big cities and secondary data analysis, this study identifies various obstacles faced by MSMEs in accessing capital and potential solutions. The results show that limited collateral, lack of credit history, and administrative procedure complexity remain the main barriers for MSMEs' access to formal financial institutions. Meanwhile, non-formal financial institutions are more accessible but often at higher costs. This research recommends strengthening financial literacy, innovation in credit guarantee schemes, and revitalizing cooperation between formal and non-formal financial institutions to improve MSMEs' access to capital.